Granulin levels in patients with idiopathic premature ovarian failure. (October 2015) - Ersoy, Ali Ozgur; Oztas, Efser; Ersoy, Ebru; Ozler, Sibel; Ergin, Merve; Yilmaz, Nafiye
Abstract: Objective: With the prolongation of expected lifespan, premature ovarian failure (POF) has gained increased significance as a crucial female health problem. Here we aimed to investigate the diagnostic value of the levels of the growth factor Granulin, which has been associated with epithelial ovarian carcinoma, in the pathogenesis of POF. Study design: Thirty-one patients with POF and 57 patients as a control group were recruited for this study in a tertiary referral center in the capital of Turkey. Granulin levels and individual characteristics of the two groups were compared. Results: Age and body mass indices were similar between the two groups. Granulin levels in patients with POF (2.94 ± 1.91 ng/mL) were significantly lower than in the control group (4.77 ± 1.62 ng/mL) ( p < 0.001). Conclusion: Future larger studies should focus on Granulin levels and its correlation with ovarian reserve markers, its clinical applicability, and its possible therapeutic value, thus providing further insight into the role of Granulin in the pathogenesis of POF.